THE ROLE OF UZBEK FOLK TALES IN THE SPIRITUAL DEVELOPMENT OF PRESCHOOL CHILDREN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This scientific article provides a comprehensive analysis of the role of Uzbek folk tales in the spiritual and moral education of preschool children, their pedagogical-psychological significance, and didactic potential. In today's conditions, where issues of spiritual upliftment and national self-awareness are acquiring priority in society, the specific features of instilling folk wisdom into a child's consciousness at the initial stage, when the foundation of personality is formed, are revealed. The article scientifically and theoretically substantiates the mechanisms through which fairy tales influence the formation of a child's worldview, creating initial conceptions of moral categories such as good and evil, kindness and wickedness, justice and injustice.